Two genders, different roads? comparing talent development pathways between female and male elite football players in Brazil - Machado, G.; González-Víllora, S.; Teoldo, I. (International Journal of Sports Science & Coaching, 2025)
The purpose of this study was threefold: 1) to compare the engagement in various types and amounts of football activities during childhood and adolescence between female and male Brazilian elite youth football players; 2) to test what talent development pathway characterizes youth development in female and male players; and 3) to compare the practice structure between both genders. Participants were 180 U-18 elite football players (98 female, 82 male) competing in the national league. The Participant History Questionnaire measured football activities across childhood (6-12 y/o) and early adolescence (13-15 y/o). Female players-initiated football activities (play, practice, competition, and 11 × 11 games) later and were less involved in structured football activities during childhood and early adolescence than males (p < .05). Conversely, female players accumulated similar futsal hours in childhood and significantly more in early adolescence (p < .05). Despite males accumulating greater overall practice volume, both genders exhibited a very similar percentual practice structure (e.g., individual, pair, and group tactics). We concluded that U-18 Brazilian elite youth football players differ in milestones and engagement in practice activities. However, despite varying participation amounts, the talent development pathways for both genders were characterized by the specialized sampling model.